Value addition to locally produced soybean in Ghana: production of soy sauce using starter culture fermentation (Journal of Science and Technology, 2016)
Ghana produces about 50,000 metric tons of soy beans per annum, of which only about 15 metric tons are utilized. One aspect of utilizing the beans is in the production of soy sauce, a product whose demand is on the increase due to changing food habits of the Ghanaian society. A preliminary attempt to produce soy sauce from the cultivated beans using starter culture fermentation approach was therefore investigated. A mixture of cooked soybean mash and roasted wheat was inoculated with Aspergillus oryzae (ATCC 46240) under aseptic conditions and allowed to ferment for five days. This fermented solid mash referred to as “koji” was then mixed with an eighteen per cent brine solution and subjected to further fermentation for three months to constitute the “moromi” stage of soy sauce production. At the end of fermentation, the “moromi” was filtered and coloured with either caramel or molasses. Chemical and sensory analysis on the resultant product showed it to be comparable and in some instances superior to commercial products on the market. This simple biotechnological method could be used to add value to surplus soy beans on the Ghanaian market.